Modelling and optimization of the firing zone of a tunnel kiln to predict the optimal feed locations and mass fluxes of the fuel and secondary air - MANÇUHAN, EBRU; KÜÇÜKADA, KURTUL (ELSEVIER SCI LTD, 2009)
Optimization of the firing zone was done to minimize the fuel cost as being the objective function by finding the optimal operating variables. These variables are the initial admixed coal (AC) in the brick body, the mass flux and locations of pulverized coal (PC) and the secondary air required for complete combustion. The constraints are the carbon coming from the AC which increases the porosity of the bricks, and should be consumed completely. Two other constraints to avoid thermal shock are the temperature difference between bricks and air, and the maximum heating rate of the bricks. The results were compared to the plant data. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Firing zone; Tunnel kiln; Optimization; Pulverized coal; Admixed coal